Effects of perfluoroalkyl substances on the operational efficiency, microbial communities, and key metabolic pathways of constructed rapid infiltration system with coke as filler layer. (June 2023) - Li, Xinjuan; Huang, Xian; Fan, Shuo; Su, Chengyuan; Ding, Fengxiu; Wen, Shitong; Li, Daoning; Chen, Menglin
Graphical abstract: Highlights: The influence of PFOA/PFBA on constructed rapid infiltration was investigated. PFOA inhibited the removal of pollutants by the constructed rapid infiltration. PFBA up-regulated the abundances of pmoA/B/C-amoA/B/C and hao . PFOA and PFBA decreased the expression of ribose 5-phosphate isomerase gene. Abstract: Influences of perfluoroalkyl substances on the performance and microbial metabolic pathways of constructed rapid infiltration systems are not fully understood. In this study, wastewater containing different concentrations of perfluorooctanoic acid (PFOA)/perfluorobutyric acid (PFBA) was treated in constructed rapid infiltration systems with coke as filler. The addition of 5 and 10 mg/L PFOA inhibited the removal of chemical oxygen demand (COD) (80.42%, 89.27%), ammonia nitrogen (31.32%, 41.14%), and total phosphorus (TP) (43.30%, 39.34%). Meanwhile, 10 mg/L PFBA inhibited TP removal of the systems. Based on X-ray photoelectron spectroscopy, the percentages of F - within the PFOA and PFBA groups were 12.91% and 48.46%, respectively. PFOA transformed Proteobacteria (71.79%) into the dominant phyla of the systems, whereas PFBA enriched Actinobacteria (72.51%). The PFBA up-regulated the coding gene of 6-phosphofructokinase by 14.44%, whereas PFOA down-regulated it by 4.76%. These findings provide insights into the toxicity of perfluoroalkyl substances on constructed rapid infiltration systems.